Inflammatory myofibroblastic tumor in the liver: a case report - Meng, Yinying; Xie, Jinlan; Liang, Yan; Wu, Mulan; Lu, Yi; Lu, Qian (Frontiers in Oncology, 2024)
Hepatic inflammatory myofibroblastic tumor (IMT) is an infrequent tumor with potential malignancy. However, it lacks specific clinical symptoms and usual imaging features.A 34-year-old woman had a six-month history of fever and on-and-off pain in the upper right part of her abdomen that lasted for two weeks. Imaging tests revealed a liver mass initially thought to be liver malignancy, but subsequent histopathological examination after liver removal confirmed the diagnosis as hepatocellular inflammatory myofibroblastic tumor (HIMT).Hepatic inflammatory myofibroblastic tumor (IMT) is an uncommon growth with vague clinical symptoms and lab results. Surgical removal remains the primary treatment method, resulting in favorable prognostic outcomes.